Case Report: A pharmacist-led precision therapy framework for managing invasive fungal infection in CSF1R-Related leukoencephalopathy post Allo-HSCT - Lu, Jin; Jia, Mengqi; Luan, Xinghua; Zhang, Zhongqiu; Wu, Jingying; Huang, Xiaojun; Yang, Li; Zhao, Xincai; Zhou, Miaomiao; Fu, Yao; Yang, Quanjun; Zhang, Jianping; et al. (Frontiers in Pharmacology, 2025)
IntroductionHereditary diffuse leukoencephalopathy with spheroids (HDLS), caused by CSF1R mutations, is a rare autosomal dominant leukodystrophy characterized by rapid neurological decline. Hematopoietic stem cell transplantation (HSCT) is a promising treatment, but the risk of post-transplant complications such as invasive fungal disease (IFD) remains underexplored. Microglial dysfunction in CSF1R-related disorder (CRD) may further impair host immune defense.MethodsWe describe a Chinese male with a non-hotspot CSF1R mutation (c.2443-1G>C) who underwent allogeneic HSCT. A multidisciplinary team (MDT), including clinical pharmacists, implemented an individualized pharmacological strategy for antifungal management, guided by immune status, infection risk, pharmacokinetics, and next-generation pathogen diagnostics.ResultsDespite prophylaxis with voriconazole and levofloxacin, the patient developed febrile neutropenia and otitis media by day +16. Empirical meropenem therapy was ineffective, prompting escalation to teicoplanin and caspofungin. Pulmonary infection developed; targeted sequencing of bronchoalveolar lavage identified Aspergillus flavus. Antifungal therapy was intensified with voriconazole, resulting in clinical resolution by day +70. Treatment was maintained with good response.DiscussionThis case demonstrates the complexity of managing IFD in CSF1R-related disorder patients after HSCT. The interplay between systemic immunosuppression and intrinsic microglial dysfunction may heighten infection susceptibility. Precision antifungal therapy guided by multidisciplinary team expertise and pharmacological monitoring may improve outcomes in this rare and high-risk population.